Effects of carotenoids on lipid bilayers. Issue 5 (19th January 2018) - Johnson, Quentin R.; Mostofian, Barmak; Fuente Gomez, Gabriel; Smith, Jeremy C.; Cheng, Xiaolin
Abstract : Carotenoids have been found to be important in improving the integrity of biomembranes in eukaryotes. Abstract : Carotenoids have been found to be important in improving the integrity of biomembranes in eukaryotes. However, the molecular details of how carotenoids modulate the physical properties of biomembranes are unknown. To this end, we have conducted a series of molecular dynamics simulations of different biologically-relevant membranes in the presence of carotenoids. The carotenoid effect on the membrane was found to be specific to the identity of the carotenoid and the composition of the membrane itself. Therefore, different classes of carotenoids produce a different effect on the membrane, and different membrane phases are affected differently by carotenoids. It is apparent from our data that carotenoids do trigger the bilayer to become thinner. The mechanism by which this occurs depends on two competing factors, the ability of the lipid tails of opposing monolayers to either (1) compress or (2) interdigitate as the bilayer condenses. Indeed, carotenoids directly influence the physical properties via these two mechanisms, thus compacting the bilayer. However, the degree to which these competing mechanisms are utilized depends on the bilayer phase and the carotenoid identity.